2013
DOI: 10.2215/cjn.05360512
|View full text |Cite
|
Sign up to set email alerts
|

1,25-(OH)2D-24 Hydroxylase (CYP24A1) Deficiency as a Cause of Nephrolithiasis

Abstract: SummaryBackground and objectives Elevated serum vitamin D with hypercalciuria can result in nephrocalcinosis and nephrolithiasis. This study evaluated the cause of excess 1,25-dihydroxycholecalciferol (1a,25(OH) 2 D 3 ) in the development of those disorders in two individuals.Design, setting, participants, & measurements Two patients with elevated vitamin D levels and nephrocalcinosis or nephrolithiasis were investigated at the National Institutes of Health (NIH) Clinical Center and the NIH Undiagnosed Disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
123
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(131 citation statements)
references
References 47 publications
(42 reference statements)
2
123
0
6
Order By: Relevance
“…The second patient was described as a 38-year-old man, with recurrent (calcium phosphate) renal stones since the age of 25 and hyperkalaemia, hypercalciuria, suppressed PTH and elevation of 1,25(OH) 2 vitamin D. He also had bi-allelic mutations, a c.1226T>C, p.L409S change inherited from his mother and the c.428_430del; p.E143del mutation inherited from his father. Metabolic studies in both patients confirmed reduced enzyme function with undetectable activity of CYP24A1 15 .…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…The second patient was described as a 38-year-old man, with recurrent (calcium phosphate) renal stones since the age of 25 and hyperkalaemia, hypercalciuria, suppressed PTH and elevation of 1,25(OH) 2 vitamin D. He also had bi-allelic mutations, a c.1226T>C, p.L409S change inherited from his mother and the c.428_430del; p.E143del mutation inherited from his father. Metabolic studies in both patients confirmed reduced enzyme function with undetectable activity of CYP24A1 15 .…”
Section: Discussionmentioning
confidence: 76%
“…This evidence for CYP24A1 variants contributing to nephrolithiasis was recently strengthened by a report detailing two patients with bi-allelic mutations in CYP24A1 15 . First, a 9-year-old boy with hypercalciuria, increased 1,25(OH) 2 vitamin D and medullary nephrocalcinosis was found to have compound heterozygous mutations (c.428_430del; p.E143del, previously reported by Schlingman 13 together with c.443T>C; p.L148P).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations